Resistance to bacterial blight caused by Xanthomonas oryzae pv. oryzae in rice - NEERAJ BALA, R.K. GOEL and (Indian Phytopathology, 2004)
Studies on the nature of resistance to Xanthomonas oryzae pv. oryzae in three elite breeding lines of rice (Oryza sativa L.) revealed two dominant complementary genes for resistance in IET 15613 and a single dominant gene in IET 16081 and IET 16099. Allelic test with IR BB-4 carrying Xa 4 indicated that the resistance gene in IET 16099 may be Xa 4 while IET 15613 and IET 16081 carry undesignated dominant resistance gene(s). Allelic tests with some other known sources of BB resistance showed that genes controlling resistance in IET 15613 were non-allelic to the gene(s) in IET 8585, PR 111 and PR 114. The dominant gene conferring resistance in IET 16081 was allelic to a gene in PR 111 but non-allelic to that in IET 8585 and PR 114, whereas the reverse was true for the single dominant gene controlling resistance to BB in IET 16099.